277 RACIAL DETERMINANTS OF PREMATURE CORONARY ARTERY DISEASE AND PREDICTORS OF EARLY MORTALITY IN YOUNG, INNER-CITY PATIENTS UNDERGOING CORONARY ANGIOGRAPHY: RESULTS OF AN OPEN COHORT STUDY. (1st January 2005) - Nathan, S.; Amin, A.; Attanasio, S.; Mehta, V.; Kelly, R. F.
Abstract : Background: The epidemiology of premature coronary artery disease (CAD) is poorly defined in the inner-city population. We investigated the relationship between race, cardiac risk factors, and premature CAD risk and assessed predictors of early mortality in public health system patients. Methods: Data from 416 patients ≤ 40 years of age, undergoing coronary angiography at Cook County Hospital (1993-2001) were compiled prospectively and analyzed as an open, retrospective cohort. The primary outcome measure was mortality analyzed via Kaplan-Meier analysis. Risk of CAD (defined as ≥ 50% stenosis in ≥ 1 coronary artery) by race and cardiac risk factors were estimated using stepwise logistic regression. Angiographic data were adjudicated by blinded film review. Results: 1, 444 patient-years of follow-up were attained. Of 416 patients, 33% (136) had premature CAD, of which 96% (131) had severe CAD (≥ 70% stenosis). White patients (OR 2.56, p = .005) and patients from the Indian subcontinent (OR 2.75, p = .04), dyslipidemics (OR 3.91, p = .001), smokers (OR 2.39, p = .001), diabetics (OR 2.25, p = .008), and older patients (OR 1.017 per incremental year of age, p = .043) all evidenced increased risk for premature CAD. Total mortality at 3.47 years mean follow-up was 5.8% and was higher with severe CAD (9.2% if CAD vs 4.2% if no CAD, p = .044). Diabetes mellitus (OR 3.71 [1.13-12.2], p = .031) and systolic dysfunction (OR 3.13 [1.0-9.81], p = .05) each independently predicted mortality. Conclusions: These data suggest a previously unrecognized risk associated with certain ethnic subgroups of the inner-city population, independent of that conferred by traditional cardiac risk factors, with CAD linked to higher mortality. Diabetes and systolic dysfunction were predictive of early mortality, independent of CAD.